Factors affecting feeding choices in infants and toddlers in northern Jordan: A cross-sectional study - Wajdi Amayreh; Mohammad Al-Magableh; Jomana Alsulaiman; Mahdi Alshboul; Maan Amayreh; Ahmad Al-Maqableh; Razan Qasem; Tamara Al-Nemrat (PLoS ONE, 2026)
Background Breastfeeding is a key determinant of infant health and survival; however, exclusive breastfeeding (EBF) rates remain low worldwide. Various maternal, infant, and socioeconomic factors influence the feeding practices. Objective The main objective of this study was to identify maternal, infant, and socioeconomic determinants of infant feeding practices during the first six months of life among mothers in northern Jordan. Methods A prospective cross-sectional study was conducted at Princess Rahma and Prince Rashid Hospitals in Irbid City, northern Jordan, from December 2023 to February 2024. Mothers of healthy infants aged 6–24 months participated in a survey that gathered information on their demographics, feeding practices, and other infant-related details. Statistical analyses were performed to identify the associations and key predictors of feeding type. Results Among the 508 mothers who participated in this study, 29.9% were exclusively breastfeeding, 46.5% used mixed feeding, and 23.6% opted for formula feeding. The key factors influencing these choices include maternal health issues, work hours, and infant birth weight. Maternal illness was identified as the strongest predictor of exclusive artificial feeding (AOR = 12.72; 95% CI: 4.10–39.45; P < 0.001). Low birth weight (<2.5 kg) was also associated with higher odds of artificial feeding (AOR = 4.75; 95% CI: 2.08–10.88; p < 0.001). Maternal employment significantly increased the likelihood of mixed feeding compared with EBF (AOR = 3.54; 95% CI: 1.65–7.60; p = 0.001). Surprisingly, no significant correlation was found between maternal education, family income, cultural factors, and feeding methods. Conclusion This study highlighted the low exclusive breastfeeding rate, emphasizing the need for improved support systems to encourage breastfeeding in the form of workplace accommodations and healthcare counseling to address barriers to its practice.